2022
DOI: 10.7196/samj.2022.v112i7.16434
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and thrombosis outcomes in hospitalised COVID-19 patients on low-molecular-weight heparin and antiplatelet therapy

Abstract: Background. An increased incidence of thromboembolic events in hospitalised COVID‐19 patients has been demonstrated despite the use of low‐molecular‐weight heparin (LMWH). Antiplatelet therapy prior to admission and early in the disease course has been hypothesised to be protective against thrombosis.Objectives. To describe the bleeding and thrombosis outcomes in hospitalised patients with confirmed COVID‐19 receiving LMWH, with and without concomitant antiplatelet therapy. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Of the currently available anticoagulants, low‐molecular‐weight heparin (LMWH) is most commonly used to improve the success rate of IVF/ICSI 23 . LMWH, also known as dalteparin, enoxaparin, or nadroparin calcium, is a class of anticoagulants with an average molecular weight less than 8000 Da that acts by binding to and activating antithrombin, thereby inhibiting factor Xa 24 . Studies have found that LMWH improves pregnancy outcomes by regulating the physiological processes required for blastocyst adhesion, implantation, and trophoblast invasion 18,19,25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the currently available anticoagulants, low‐molecular‐weight heparin (LMWH) is most commonly used to improve the success rate of IVF/ICSI 23 . LMWH, also known as dalteparin, enoxaparin, or nadroparin calcium, is a class of anticoagulants with an average molecular weight less than 8000 Da that acts by binding to and activating antithrombin, thereby inhibiting factor Xa 24 . Studies have found that LMWH improves pregnancy outcomes by regulating the physiological processes required for blastocyst adhesion, implantation, and trophoblast invasion 18,19,25 .…”
Section: Introductionmentioning
confidence: 99%
“… 23 LMWH, also known as dalteparin, enoxaparin, or nadroparin calcium, is a class of anticoagulants with an average molecular weight less than 8000 Da that acts by binding to and activating antithrombin, thereby inhibiting factor Xa. 24 Studies have found that LMWH improves pregnancy outcomes by regulating the physiological processes required for blastocyst adhesion, implantation, and trophoblast invasion. 18 , 19 , 25 However, a meta‐analysis 23 evaluating the effect of LMWH on pregnancy outcomes in non‐thrombophilic women undergoing IVF/ICSI treatment showed that administration of LMWH did not affect pregnancy success.…”
Section: Introductionmentioning
confidence: 99%